Perverse incentives: How the reward structures of academia impede scholarly communication and good science - Gowers, Timothy (Septentrio Conference Series, 2017)
Watch the VIDEO here. There is widespread agreement that our practices of scholarly communication are a long way from being optimal, and that this has become particularly true in the last twenty years. In principle, the internet should make dissemination almost free and allow for new forms of communication such as "grey literature" and the sharing of data. And yet, while the internet has undoubtedly changed all our lives for the better, articles in conventional and extremely expensive journals continue to be the dominant means of communication, and it has proved to be very difficult to change the system to take advantage of the new opportunities. I shall discuss the various incentives that give the current system its robustness, and make a few suggestions for how they can be weakened. To do this I shall draw on my own experiences of campaigning for change, and also report on some important changes that have already taken place in the communication practices of mathematicians.